Safety and efficacy of a feed additive consisting of Lacticaseibacillus rhamnosus CNCM I‐3698 and Companilactobacillus sp. CNCM I‐3699 for chickens for fattening (STI Biotechnologie) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Birgit Dusemund; Mojca Durjava; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal)
Abstract Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of Sorbiflore® ADVANCE, a feed additive consisting of Lacticaseibacillus rhamnosus CNCM I‐3698 and Companilactobacillus sp.CNCM I‐3699 intended to be used as a zootechnical additive (functional group: other zootechnical additives) in feed for chickens for fattening to improve their performance. In a previous opinion, the additive was described as containing viable but not cultivable cells of the two strains in a 1:1 ratio, with a minimum of total lactic acid bacteria counts of 5 × 108 viable forming units (VFU)/g additive. However, in that opinion, the Panel could not fully characterise the additive or conclude on its dermal/ocular irritancy or sensitisation potential. In the current assessment, the applicant provided supplementary information to address the missing information for the characterisation of the additive. The proposed methodology to discriminate and individually quantify the two strains composing the additive still presented limitations. Therefore, the Panel concluded that the data available do not allow to fully characterise the additive. The Panel was not in the position to conclude on the taxonomical identification of the strain CNCM I‐3699, and consequently, on its eligibility for the application of the qualified presumption of safety (QPS) approach. Therefore, the previous conclusions on the safety of the additive based on the QPS approach could not be confirmed. The Panel was not in the position to conclude on the safety of the additive for the target species, consumer and the environment. Sorbiflore® ADVANCE is not irritant to skin. The Panel could not conclude on the eye irritancy or skin sensitisation potential of the additive.